Perceived Severity of COVID-19 and Post-pandemic Consumption Willingness: The Roles of Boredom and Sensation-Seeking - Deng, Shichang; Wang, Wangshuai; Xie, Peihong; Chao, Yifan; Zhu, Jingru (Frontiers in Psychology, 2020)
The COVID-19 pandemic restricts people’s activities and makes consumer businesses suffered. This study explored the relationship between the perceived severity of COVID-19 and the post-pandemic consumption willingness. Study 1 surveyed 1464 Chinese people in March 2020, found the perceived severity of COVID-19 during the pandemic significantly increased the willingness to consume post-pandemic, and boredom stemming from limited activities and sensation-seeking expressions mediated this effect. Study 2 conducted an experiment with 174 participants in August 2020, found a high level of perceived severity of COVID-19 and the experience of life tedium during the pandemic significantly increased individuals’ impulsive buying tendencies after the pandemic. The results suggested the level of perceived severity of COVID-19 may influence people’s post-pandemic consumption patterns.